The effect of remote training during COVID-19 quarantine on body composition changes in collegiate football players - Stowers, L.; Fernández, J. R. (International Journal of Sports and Exercise Medicine, 2021)
Background: Previous research has shown that following a structured training plan can result in significant changes in body composition in elite football players. However, the effect on body composition changes after athletes complete the same training plan remotely with limited resources needs further investigation. Aim: The purpose of this study is to determine if body composition changes in collegiate football players differ after training remotely during COVID-19 quarantine compared to training on campus during a routine off-season training period. Methods: This study was conducted as a secondary analysis of routine data collection in a southeastern collegiate athletic department. Body composition data was collected during off-season training in two separate groups of collegiate football players. Group 1 data was collected before and after the COVID-19 quarantine forced athletes to replicate their training remotely. Group 2 data was collected before and after a typical off-season training program on campus. Changes in body composition over the training period were calculated for each group and analyzed for statistical differences. Results: Anova was used to analyze the changes in weight, body fat, muscle mass, and BMI changes between groups. Results showed a significant change in muscle mass between groups 1 and 2 (F = 2.53, p = 0.0012). Conclusion: These results suggest that training remotely may not be as effective in building muscle mass when compared to traditional on campus training. Additionally, on campus resources such as coaches, support staff, nutrition, and community training may influence training results.